DEVELOPMENT OF A WEB-BASED TRIGONOMETRY E-MODULE WITH A MINDFUL LEARNING APPROACH - Rosyid, Muhammad Haniif Khoirulloh; Handayani, Aprilia Dwi; Santia, Ika (Jurnal Ilmiah Pendidikan Citra Bakti, 2026)
This research aims to develop a web-based trigonometry learning medium using a mindful learning approach for Grade X students at SMK Hang Tuah Kediri. The study analyzes the feasibility, practicality, and effectiveness of the medium in supporting student learning outcomes. The method employed is Research and Development (R&D), adapting the ADDIE model. The research stages include needs analysis, design, product development, expert validation, and field testing with 17 Grade X students. Validation results showed a very high level of validity with a Gregory coefficient of 1.00. The medium was declared feasible without substantial revision as the material structure aligns with the Learning Path Objectives at SMK Hang Tuah Kediri. The depth of the material was considered highly relevant to basic competency indicators, achieving a perfect score in both content and construction aspects. In terms of practicality, student and teacher responses reached an average of 91.82%, categorized as highly practical. Meanwhile, the effectiveness of the medium, based on learning evaluation results, showed an average N-Gain value of 49.41%. This value falls within the 40–59% range, categorized as moderately effective. Pedagogically, this achievement indicates that the medium is capable of facilitating the transition of students' understanding of trigonometric concepts from basic to complex levels, although teacher guidance remains necessary for optimal results.